Knowledge, attitudes and practices towards COVID-19 prevention measures among private clinic patients in Windhoek, Namibia - Ntumba, Alexis; Oyedele, Opeoluwa; Kazembe, Lawrence (Namibian Journal for Research, Science and Technology, 2022)
In December 2019, the SARS-CoV-2 virus emerged in Wuhan, Hubei Province, China, and later spread rapidly to other parts of China and eventually across all countries around the world, including Namibia. Despite causing severe to fatal acute respiratory syndrome, there are no known cures for the SARSCoV-2 virus, only preventive measures such as social distancing, hands sanitizing, hands washing, wearing masks, and full-dosed COVID-19 vaccination. For this reason, this study was aimed at assessing the Knowledge, Attitudes and Practices (KAP) towards COVID-19 prevention measures among private clinic patients in Windhoek during 1 October to 30 November 2021. A cross-sectional analytic study using quantitative method was used with data collected in a single round among patients visiting two private clinics in Windhoek. Results showed that more than half (62%) were females, 58.5% were single and 70% attended tertiary education and 71% were employed as of 30 November 2021. In addition, at least 90% of the participants knew each of the COVID-19 prevention measures, while more than three-quarters (79%) had comprehensive knowledge of the measures, with 65% of them knowing that one needs two shots of the COVID-19 vaccine for immune protection against the virus. At least 90% of the participants were in favour of practicing each COVID-19 prevention measure, while more than three-quarters (81.5%) had comprehensive positive attitude towards the measures in general. However, less than half (48%) of the participants believed that the COVID-19 vaccines can prevent one from the virus. Moreover, more than 95% of the participants were practicing each COVID-19 prevention measures, with 90% practicing all the prevention measures at the same time, with the exception of the COVID-19 vaccination as only 37% of the participants were vaccinated. Seeing as the participants had very good knowledge, attitudes and practices towards COVID-19 prevention measures, with barely more than a quarter of them vaccinated against COVID-19, the health education and awareness of COVID-19 in the country must continue in order to maintain the very good KAP of its prevention measures in Windhoek.